Kinerja Tim sebagai Mediator antara Kepemimpinan Digital dan Tangkas terhadap Kelincahan Organisasi dan Perilaku Kerja Inovatif pada OPD Provinsi Sulawesi Barat - Adnan, Adnan; Ramli S, Ramli S; Aqil, Muhammad; Abdullah, M Said (Journal of Management Branding, 2026)
The study employed an explanatory quantitative approach through a survey of 50 employees engaged in team-based work. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with a bootstrapping technique of 5,000 resamples. The findings indicate that Agile Leadership has a significant effect on Team Performance, whereas Digital Leadership does not exert a direct significant effect. Furthermore, Team Performance significantly influences Organizational Agility and Innovative Work Behavior and functions as a mediator in the relationship between leadership and organizational outcomes. These results underscore that digital transformation in the public sector does not rely solely on technological orientation but primarily on adaptive leadership dynamics and the effectiveness of team performance as an operational mechanism of dynamic capabilities